2018
DOI: 10.7824/rbh.v17i1.551
|View full text |Cite
|
Sign up to set email alerts
|

Biochar impact on herbicides behavior in the soils: an approach in Brazil

Abstract: A aplicação de biochar (biocarvão) em solos por causa dos efeitos benéficos é comprovada por muitos pesquisadores internacionais e isto pode aumentar a sorção dos herbicidas e reduzir a eficácia destes no manejo das plantas daninhas. Impactos positivos são relatados em relação ao comportamento ambiental dos herbicidas, pois o aumento da sorção reduz a lixiviação destes produtos para as águas subterrâneas. Impactos negativos são relatados em relação ao manejo agronômico dos herbicidas, pois o aumento da sorção … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The obtained hydrolate was centrifuged at 5,000 rpm for 3 min to promote the separation between the aqueous and oily phases. With the aid of a Pasteur pipette, the (supernatant) oil was removed and stored in an amber bottle in a freezer at − 20 °C, protected from light 4,29 .…”
Section: Materials and Methods Plant Materialmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained hydrolate was centrifuged at 5,000 rpm for 3 min to promote the separation between the aqueous and oily phases. With the aid of a Pasteur pipette, the (supernatant) oil was removed and stored in an amber bottle in a freezer at − 20 °C, protected from light 4,29 .…”
Section: Materials and Methods Plant Materialmentioning
confidence: 99%
“…The relative percentage of each essential oil compound was calculated by the ratio between the total area of the peaks and the total area of all constituents of the sample, obtained by GC-FID analysis. Compounds with a relative area above 1% were identified, and those over 5% were considered to be major 29 .…”
Section: Materials and Methods Plant Materialmentioning
confidence: 99%
“…However, OM and clay are closely related to sorption of herbicides in soil. The OM is not only the main site where bound residues are formed, but also, similar to the clay, it has a high specific surface area that can strongly retain the herbicides, so the bioavailability of the product in the soil solution is lower, resulting in lower weed control efficiency [29].…”
Section: Oxyfluofenmentioning
confidence: 99%
“…In addition to the straw, the use of exogenous OM in cropping systems, such as the application of biochar (coal derived from vegetal biomass), has affected the retention and dynamics of herbicides in the soil. This is due to the high OC contents, higher surface areas and more porous structures, which result in higher herbicide sorption capacities (Mesa and Spokas, 2011;Mendes et al, 2018b). Several studies have indicated higher sorption of herbicides, such as atrazine, MCPA, aminocyclopyrachlor and terbuthylazine in soils modified with biochar and bonechar (Wang et al, 2010;Martin et al, 2012;Tatarková et al, 2013;Cabrera et al, 2014).…”
Section: Organic Matter Of the Soil In Retention Of Herbicidesmentioning
confidence: 99%